(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Conversion of agricultural waste to useful product especially activated carbon will reduce thedemand for new resources cut down the cost and effort to transport and production, otherwise loss tolandfill. Due to abundant supply, high density and purity, brew waste is chosen with the appropriatemethod of activation the widely used non-hazardous carbonbearing product ―Activated Carbon‖ (AC) isproduced. Dual surface modification namely chemical activation with sulphuric acid followed byultrasonication clinches the properties of activated carbon. Chitosan is a second-most abundantbiopolymer on earth after cellulose. Its unique properties have recently received particular attention fromresearchers to be used as a potential biosorbent for the removal of organic dyes. However, purechitosan has some limitations that exhibit lower biosorption capacity, surface area and thermal stabilitythan chatoyant composites.